Design and Control of a Three-Phase T-Type Inverter using Reverse-Blocking IGBTs - Tuan, D. A.; Vu, P.; Lien, N. V. (Engineering, Technology & Applied Science Research, 2021)
This paper proposes the design and implementation of a 15kW three-phase T-type inverter. Fuji Electric’s new generation IGBT module (V series) using RB-IGBT technology is applied for the converter, due to its higher efficiency from conventional IGBTs to reduce switching losses on the semiconductors. Under full load conditions, the overall efficiency of the converter can reach over 98%. The control design and sine PWM modulation are implemented on a DSP kit named TMS320F3F28379D. In addition, the PWM is generated with the fundamental and third harmonics of a sin wave, allowing a modulation factor up to 1,154 compared to traditional PWM. The output voltage of 220V/50Hz with less than 2% of THD can be achieved at the minimum input DC voltage of 550V.